Leadership for learning : how to help teachers succeed - Glickman, Carl D. (Alexandria, Va. : Association for Supervision and Curriculum Development, 2002)
In a follow-up to his earlier book on Developmental Supervision, distinguished educator and author Carl D. Glickman provides instructional leaders-supervisors, principals, and teachers-with practical guidance and thoughtful insight to help them succeed as they work with teachers to improve classroom teaching and learning. In a straightforward and easy-to-read manner, Glickman discusses . Structures of classroom assistance-clinical supervision, peer coaching, critical friends, and action research groups; . Formats for observations-frameworks for teaching, open-ended questionnaires, samples of student work, and student achievement on high-stakes tests; and . Approaches to working directly with teachers-directive, collaborative, and nondirective. Scenarios that describe interactions with teachers of diverse backgrounds and skill levels bring the various approaches to life. The author also provides useful information on summative and formative evaluation of teachers. In addition to forms and examples that readers can duplicate or adapt to their own situation, the book includes an extensive list of resources on the topics of looking at student work, professional development and instructional leadership, and educators' ethnic, cultural, and personal diversity. Leadership for Learning goes beyond the basics of supervision to place the work of instructional leadership within the context of whole-school improvement. Drawing on his years of experience in working with schools in varied settings, Glickman offers both advice and inspiration to instructional leaders who strive toward the ultimate goal of providing the best possible classroom experience for every student.
Includes bibliographical references and index.
Keywords: School supervision -- United States; Teacher effectiveness -- United States; Effective teaching -- United States